No-Show Rates and Associated Patient Factors in an Ophthalmology Resident Practice - Nanda, Tavish; Wang, Aijin; Ducasse, Luis M.; Chen, Royce W.S.; Horowitz, Jason (Journal of Academic Ophthalmology, 2020)
Background In resident family medicine practices, a >20% no-show rate is common, often resulting in suboptimal care. Few studies have evaluated resident ophthalmology practices in a similar fashion. The objective of this study was to determine no-show rates and factors related to missed appointments in a resident-based ophthalmology clinic.Methods We reviewed 19,237 de-identified appointments over one academic year. Appointments were divided into general clinic visits and subspecialty visits (these two clinics function separately at our institution). The number of days between an appointment being made for a patient and the scheduled visit was defined as “lead time.” Each appointment was labeled “show” or “no-show.” Pertinent factors available in the analysis included lead time to appointment, patients age, month, time of day, practitioner training level (postgraduate years 2 to 4, fellow), and proximity to holiday. Subspecialty clinics included oculoplastics clinic, strabismus clinic, neuro-ophthalmology clinic, uveitis clinic, cornea clinic, glaucoma clinic, and retina clinic. Generalized linear mixed effects models were fit on the no-show status with these factors.Results The overall no-show rate for general clinic was 31.4%. Longer lead time to appointment, younger age, afternoon appointments, new patients, December appointments, and lower residency level were associated with higher odds of no-show (p ≤ 0.05). The overall no-show rate for subspecialty clinic was 21.8%. Longer lead time to appointment, younger age, and lower residency level were associated with higher odds of no-show (p ≤ 0.05). Patients were significantly less likely to show up for retina clinic, oculoplastics clinic, and glaucoma clinic.Conclusion The overall no-show rate in our clinic was on the higher end of reported no-show values from other specialties. Patient status and the lead time to appointment play a significant role in patient compliance. The significance of other factors (patient age, subspecialty, time of day, appointment month, and resident level) have been found in previous studies but are not consistent factors across all clinical environments.
Keywords: quality improvement; no-show rates; follow-up; appointment; scheduling; social services; revenue